2013
DOI: 10.1021/ac400556q
|View full text |Cite
|
Sign up to set email alerts
|

Improved EIS Performance of an Electrochemical Cytosensor Using Three-Dimensional Architecture Au@BSA as Sensing Layer

Abstract: An ultrasensitive electrochemical cytosensor for quantitative determination of carcinoembryonic antigen (CEA)-positive tumor cells was developed using three-dimensional (3D) architecture Au@BSA microspheres as sensing layer with the conjugation of targeting molecule monoclonal anti-CEA antibody (anti-CEA). The prepared Au@BSA microspheres exhibited satisfactory biocompatibility for cell proliferation via evaluation from thiazolyl blue tetrazolium bromide (MTT) assay, providing a suitable platform for cell adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 48 publications
0
56
0
Order By: Relevance
“…The results indicated that GOx entrapped in the nanocomposites has an unchanged secondary structure and retains its biological activity. Electrochemical impedance spectroscopy (EIS) is a highly effective tool to measure the change of interface properties of the modified electrode surface during the fabrication process [31]. Figure 4( 6 ].…”
Section: Characterization Of Fe 3 O 4 -Rgo Nanocompositesmentioning
confidence: 99%
“…The results indicated that GOx entrapped in the nanocomposites has an unchanged secondary structure and retains its biological activity. Electrochemical impedance spectroscopy (EIS) is a highly effective tool to measure the change of interface properties of the modified electrode surface during the fabrication process [31]. Figure 4( 6 ].…”
Section: Characterization Of Fe 3 O 4 -Rgo Nanocompositesmentioning
confidence: 99%
“…GA is an ideal reagent, because it reacts immediately and quantitatively with primary amino groups to give stable imines, giving chemical activation. After the immediate and quantitative reaction with GA, the R et value sharply increased to 832 Ω (curve c), because of the formation of Schiff base structures and steric hindrance of kinetic solvent effect (Hu et al, 2013b). BSA, which has a large number of functional groups (e.g., À SH and À NH 2 ) (Hu et al, 2012), can be converted to a reactive interface by GA, where another layer of target biomolecules SNA was covalently immobilized on the surface of the BSA-incorporated Ag nanoflowers via Schiff base structures, the R et value increased to 1943 Ω (curve d).…”
Section: Eis Characterization Of Cytosensor Fabricating Stepsmentioning
confidence: 99%
“…In our previous work, we synthesized a series of metal@protein nanocomposites via a protein-mediated method, and used them as sensing platforms for the sensitive detection of cancer cells (Hu et al, 2013a(Hu et al, , 2013b. These hybrid nanocomposites have a range of advantages such as excellent conductivities, large surface areas, and nontoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…However, collecting and treating these templates are rather intricate, and sometimes require some special training. Plant leaf, possessing a feature of hierarchical and porous structure, as a kind of renewable and accessible biomass, has been used as template to synthesize metal carbide (Li et al, 2009), metal oxide (Huang et al, 2014), and noble metals (Hu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%